High-performance MXene modified oxide electrolysis water electrode and application
By introducing a variety of metal elements and modified oxides to MXene to form high-performance electrode materials, the problems of high overpotential during electrolytic water catalysis and easy corrosion of the catalyst in the prior art are solved, and lower oxygen evolution overpotential and taffel slope are achieved, and catalytic efficiency and stability are improved.
Patent Information
- Application Number
- CN202510116440.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the overpotential during electrolytic water catalysis is high, making it difficult to meet the demand for electrolytic alkaline seawater, and the catalyst is susceptible to chloride ions corrosion, resulting in a decrease in activity.
Using MXene as the matrix, a unique microstructure is formed by introducing a variety of metal elements and modified oxides, thereby improving the catalytic performance and stability of the electrode material. The specific steps include preparing Ti3AlC2 MAX powder, forming a multi-layer accordion-like Ti3C2Tx MXene by solvothermal method and heat treatment, then reacting with metal salts and organic ligands to form a reaction precursor, and annealing under an air atmosphere to obtain a high-performance MXene modified oxide electrode.
It significantly reduces the oxygen evolution overpotential and taffel slope, improves the catalytic efficiency and kinetic conditions, enhances the stability and corrosion resistance of the electrode material, and maintains high activity during long-term operation.
Smart Images

Figure CN119663366A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, and specifically to a high-performance MXene-modified oxide water electrolysis electrode and its application. Background Art
[0002] Hydrogen is considered to be one of the effective energy sources to replace fossil fuels due to its high energy density and no CO2 emissions during energy conversion and use. Electrochemical seawater splitting technology driven by renewable electricity and catalyzed by non-precious metal catalysts is a cost-effective green method for hydrogen production. This technology can not only alleviate the pressure on scarce freshwater resources, but also promote the large-scale industrial development of electrochemical seawater splitting technology. Although direct seawater electrolysis has potential advantages, it places more stringent requirements on membranes and electrocatalysts, especially anode OER electrocatalysts. The scientific and technological problems encountered in seawater electrolysis mainly come from Cl - Specifically, the chlorine evolution reaction (CER) competes with the oxygen evolution reaction (OER), thus reducing the electrolysis efficiency of seawater. - and its derivatives (such as hypochlorite (ClO x - )) may seriously corrode the catalyst and cause a decrease in activity.
[0003] Although noble metal electrodes such as Pt / C, IrO2 or RuO2 occupy a central position in seawater electrolysis due to their low overpotential and excellent long-term stability, their high price makes their manufacturing cost high. Therefore, the core task in this field is to focus on the development of low-cost and efficient catalysts, especially those based on elements with high earth abundance.
[0004] In the prior art, transition metal oxides (TMO) are one of the excellent seawater electrolysis catalysts due to their excellent corrosion resistance and high-valent active sites. However, most TMOs prepared by the prior art have poor intrinsic conductivity and high reaction energy barriers, especially in the process of electrolysis of alkaline seawater. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a high-performance MXene-modified oxide water electrolysis electrode and its application, so as to solve the problem in the prior art that the overpotential is high during water electrolysis catalysis and it is difficult to meet the demand for electrolysis of alkaline seawater.
[0006] In order to solve the above technical problems, this application adopts the following technical solutions:
[0007] A high-performance MXene-modified oxide water electrolysis electrode is prepared by the following steps:
[0008] Step 1: Prepare Ti3AlC2 MAX powder;
[0009] Step 2: Mix the Ti3AlC2 MAX powder prepared in step 1 with the hydrofluoric acid solution and heat to 45-50°C for reaction while stirring continuously. Wash and dry the solid material to obtain a multilayer accordion-shaped Ti3AlC2T x MXene;
[0010] Step 3: Take the Ti3AlC2T prepared in step 2 x MXene and the intercalation agent are mixed and stirred evenly to obtain a suspension, which is then centrifuged and the precipitate is repeatedly dispersed with water to obtain a two-dimensional lamellar Ti3C2T x MXene suspension; wherein the intercalation agent is tetramethylammonium hydroxide, and the mass concentration of the intercalation agent is 10wt%-15wt% calculated by mass percentage; Ti3AlC2T x The mass volume ratio of MXene to intercalant is 1 g: (10-40) mL;
[0011] Step 4: mixing the suspension prepared in step 3 with the metal salt solution and the organic ligand in a methanol solution for reaction, centrifuging the product after the reaction, taking the precipitate, repeatedly washing it and vacuum drying it to obtain a reaction precursor;
[0012] Among them, Ti3C2T x The molar ratio of MXene to the metal element in the metal salt solution is (0.5-1):5; the metal salt solution is one or a mixture of two or more of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O and Mn(NO3)2·4H2O; the organic ligand is terephthalic acid, and the concentration of the organic ligand in the reaction system is 0.3-0.4mmol / mL; the reaction temperature is 50-70°C, and the reaction time is 22-26h;
[0013] Step 5: Annealing the precursor prepared in step 4 in an air atmosphere to obtain the water electrolysis electrode.
[0014] Preferably, in step 1, Ti3AlC2 MAX powder is prepared by the following method:
[0015] The titanium powder, aluminum powder and carbon powder are uniformly mixed, and the mixed powder is sintered, crushed and ground in a weak oxidizing atmosphere to obtain Ti3AlC2 MAX powder;
[0016] The molar ratio of titanium powder, aluminum powder and carbon powder is 3:(1-1.5):(1-1.5); the gas flow rate is 150-250cm 3 / min; during sintering, the sintering temperature is 1300-1500°C and the sintering time is 6-12h; the particle size of the Ti3AlC2 MAX powder obtained by sintering is 50-100μm; the weak oxidizing atmosphere is calculated according to mass percentage, and the oxygen content in the atmosphere is less than 0.001%.
[0017] Preferably, in step 1, the heating rate from room temperature to 1200° C. is 10° C. / min, and the heating rate from 1200° C. to the sintering temperature is 2° C. / min.
[0018] Preferably, in step 2, calculated by mass percentage, the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 40% to 50%; the mass volume ratio of Ti3AlC2 MAX powder to hydrofluoric acid solution is 1 g: (10 to 20) mL; and the reaction time is 48 h.
[0019] Preferably, in step 3, the suspension is centrifuged to obtain a supernatant having a pH value of 6-8.
[0020] Preferably, in step 4, when there are any two metal elements in the metal salt solution, the molar ratio of the two metal elements is (1-1.2):(1-1.2); when there are any three metal elements in the metal salt solution, the molar ratio of the three metal elements is (1-1.2):(1-1.2):(1-1.2); when there are any four metal elements in the metal salt solution, the molar ratio of the four metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2); when there are five metal elements in the metal salt solution, the molar ratio of the five metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2).
[0021] Preferably, in step 4, Ti3C2T x The molar ratio between MXene and Fe, Co, Ni, Cu, and Mn is (0.5~1):(1~1.2):(1~1.2):(1~1.2):(1~1.2):(1~1.2).
[0022] Preferably, in step 5, the annealing temperature is 500-800° C., the heating rate is 3-6° C. / min, and the holding time of the annealing treatment is 1-3 h.
[0023] Preferably, the average particle size of the electrode material is 30 to 50 nm.
[0024] The present application also provides an application of a high-performance MXene-modified oxide water electrolysis electrode, wherein the electrode is used as a catalyst for electrolysis of water or electrolysis of seawater.
[0025] Compared with the prior art, this application has the following beneficial effects:
[0026] 1. This application is based on MXene, and by introducing modified oxides thereon, a unique microstructure design is formed, and ultimately the electrocatalytic performance of the electrode material is significantly improved; wherein, the solvothermal method is used to make the distribution of the metal elements in the electrode material more uniform, and the oxidation of the precursor is achieved by heat treatment, and the two-dimensional lamellar Ti3C2T x Mixing MXene with a metal salt solution to prepare a precursor ensures that high-density, well-dispersed oxide nanoparticles are evenly distributed on the MXene layer, which makes the electrode material have a lower oxygen evolution overpotential and Tafel slope in alkaline and alkaline simulated seawater media, indicating that the electrode material with such a structure not only increases the number of active sites, but also promotes rapid electron transfer, and the electrode material has excellent catalytic efficiency and kinetic conditions.
[0027] 2. In addition to the excellent catalytic activity of the electrode material described in the present application, the MXene-modified oxide electrode also exhibits excellent stability and corrosion resistance. Its microscopic morphology shows the polycrystalline phase characteristics of the nanoparticles in the electrode material, and the introduction of multiple metal elements in the solid solution causes lattice distortion and point defects in the electrode material. These structural design improvements help to improve the stability of the electrode material; and long-term continuous timing point potential tests have confirmed that even after long-term operation, the electrode material described in the present application still maintains a high activity; in addition, MXene's good Coulomb repulsion of chloride ions further enhances its corrosion resistance in chlorine-containing environments.
[0028] 3. The electrode material described in the present application is prepared by a simple and efficient preparation process. The process of combining solvent thermal method with heat treatment can not only achieve uniform distribution of various metal elements, but also effectively enhance the electrochemical active area, giving the electrode better conductivity and electrocatalytic performance; more importantly, the entire reaction process of the present application is easy to control and has low energy consumption, which greatly reduces production costs; compared with traditional methods, the process flow of the present application is simpler and more efficient, and has the prospect of large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a transmission electron microscope image of Example 1 of the present application.
[0030] Figure 2 This is a high-resolution transmission electron microscope image of Example 1 of the present application.
[0031] Figure 3 This is a graph showing the electrochemical oxygen evolution polarization curves obtained by linear sweep voltammetry testing of Example 1 and Comparative Examples 1-5 of the present application in an alkaline medium.
[0032] Figure 4 This is a graph of the hydrogen evolution Tafel slopes obtained by converting the linear sweep voltammetry test of Example 1 and Comparative Examples 1-5 in an alkaline medium.
[0033] Figure 5 This is a graph showing the electrochemical oxygen evolution polarization curves obtained by linear sweep voltammetry testing of Example 1 and Comparative Examples 1-5 of the present application in an alkaline simulated seawater medium.
[0034] Figure 6 This is a graph of the hydrogen evolution Tafel slope curves obtained by converting the linear sweep voltammetry test of Example 1 and Comparative Examples 1-5 in an alkaline simulated seawater medium.
[0035] Figure 7 This is the electrochemical specific surface area diagram of Example 1 and Comparative Examples 1-5 of the present application.
[0036] Figure 8 This is a stability test diagram of Example 1 and Comparative Example 1 of the present application in an alkaline simulated seawater medium.
[0037] In the figure, M-(FeCoNiCuMn)2O3 is Example 1; (FeCoNiCuMn)2O3 is Comparative Example 1; (FeCoNiCuMn)2O3 is Comparative Example 1; (FeCoNiCu)2O3 is Comparative Example 2; (FeCoCu)2O3 is Comparative Example 3; (CoCu)O is Comparative Example 4; Co3O4 is Comparative Example 5. DETAILED DESCRIPTION
[0038] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0039] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0040] 1. A high-performance MXene-modified oxide water electrolysis electrode
[0041] Step 1: Prepare Ti3AlC2 MAX powder;
[0042] Step 2: Mix the Ti3AlC2 MAX powder prepared in step 1 with the hydrofluoric acid solution and heat to 45-50°C for reaction while stirring continuously. Wash and dry the solid material to obtain a multilayer accordion-shaped Ti3AlC2T x MXene;
[0043] Step 3: Take the Ti3AlC2T prepared in step 2 x MXene and the intercalation agent are mixed and stirred evenly to obtain a suspension, which is then centrifuged and the precipitate is repeatedly dispersed with water to obtain a two-dimensional lamellar Ti3C2T x MXene suspension; wherein the intercalation agent is tetramethylammonium hydroxide, and the mass concentration of the intercalation agent is 10wt%-15wt% calculated by mass percentage; Ti3AlC2T x The mass volume ratio of MXene to intercalant is 1 g: (10-40) mL;
[0044] Step 4: mixing the suspension prepared in step 3 with the metal salt solution and the organic ligand in a methanol solution for reaction, centrifuging the product after the reaction, taking the precipitate, repeatedly washing it and vacuum drying it to obtain a reaction precursor;
[0045] Among them, Ti3C2T x The molar ratio of MXene to the metal element in the metal salt solution is (0.5-1):5; the metal salt solution is one or a mixture of two or more of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O and Mn(NO3)2·4H2O; the organic ligand is terephthalic acid, and the concentration of the organic ligand in the reaction system is 0.3-0.4mmol / mL; the reaction temperature is 50-70°C, and the reaction time is 22-26h;
[0046] Step 5: Annealing the precursor prepared in step 4 in an air atmosphere to obtain the water electrolysis electrode.
[0047] After studying the prior art, the present application found that the oxide electrodes prepared by the prior art often show a high overpotential and a large Tafel slope in the process of electrolysis of water, which limits its efficiency in practical applications; especially in the electrolysis of seawater, due to the presence of chloride ions in seawater, not only is the catalytic activity insufficient, but the electrode material is also susceptible to corrosion, resulting in a very significant decline in performance during long-term operation. Moreover, the traditional method of preparing high-performance electrode materials usually requires complex steps and high energy consumption, which is not conducive to large-scale industrial applications. Based on the above technical problems, the present application conceives an improved design of the catalyst, using MXene as a matrix, introducing a variety of metal elements thereon, increasing the number of active sites in the electrode material, and improving the overall catalytic efficiency. The present application not only successfully realizes the introduction of a variety of metal elements into MXene, but also unexpectedly finds that the obtained electrode material has excellent stability; especially after long-term electrolysis of seawater, the electrode material described in the present application can still maintain a high activity and has good corrosion resistance and stability.
[0048] In some embodiments of the present application, in step 1, Ti3AlC2 MAX powder is prepared by the following method:
[0049] Titanium powder, aluminum powder and carbon powder are mixed uniformly, and the mixed powder is sintered, crushed and ground in a weak oxidizing atmosphere to obtain Ti3AlC2 MAX powder; wherein the molar ratio of titanium powder, aluminum powder and carbon powder is 3:(1-1.5):(1-1.5); the gas flow rate is 150-250cm 3 / min; during sintering, the heating rate from room temperature to 1200°C is 10°C / min, the heating rate from 1200°C to the sintering temperature is 2°C / min, the sintering temperature is 1300-1500°C, and the sintering time is 6-12h; the particle size of the Ti3AlC2MAX powder obtained by sintering is 50-100μm; the weak oxidizing atmosphere refers to an atmosphere with extremely low oxygen content, specifically: calculated by mass percentage, the oxygen content in the atmosphere is less than 0.001%. This application adjusts the method for preparing Ti3AlC2 MAX, adopts a weak oxidizing atmosphere for sintering, controls the oxygen content inside the MAX material, avoids the generation of by-products caused by excessive oxidation, and also helps the subsequent preparation of MXene materials.
[0050] In some embodiments of the present application, in step 2, the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 40% to 50% calculated by mass percentage; the mass volume ratio of Ti3AlC2 MAX powder to hydrofluoric acid solution is 1g: (10 to 20) mL; the stirring speed is 400r / min, and the stirring time is 48h; the centrifugal speed is 5000r / min, and the centrifugal time is 30min; the standard for the completion of precipitate cleaning is that the pH value of the supernatant is between 6.0-8.0; and the vacuum drying time is 24h. The present application uses hydrofluoric acid to further adjust the microstructure of Ti3AlC2 MAX, so that it forms a multi-layer accordion shape, which can enhance the hydrophilicity of the electrode material while enhancing the electrochemical active area of the electrode material.
[0051] In some embodiments of the present application, in step 3, the suspension is centrifuged to obtain a supernatant with a pH value of 6-8; the centrifugal speed is 5000 r / min, the centrifugal time is 5 min; and the ultrasonic treatment time is 1-2 h.
[0052] In some embodiments of the present application, in step 4, when there are any two metal elements in the metal salt solution, the molar ratio of the two metal elements is (1-1.2):(1-1.2); when there are any three metal elements in the metal salt solution, the molar ratio of the three metal elements is (1-1.2):(1-1.2):(1-1.2); when there are any four metal elements in the metal salt solution, the molar ratio of the four metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2); when there are five metal elements in the metal salt solution, the molar ratio of the five metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2). The design of this application adopts the introduction of multiple elements to increase the number of active sites in the electrode material. However, it is expected that the introduction of too many metal elements will affect the stability of the electrode material in long-term operation. However, after in-depth research, it is found that this application uses five elements, Fe, Co, Ni, Cu and Mn, to increase the number of active sites in the electrode material, which can not only improve the overall catalytic efficiency of the material, but also make the electrode material have better stability in long-term operation, and this stability is even better than that of the electrode material that only introduces 1 to 4 metal elements. Therefore, the types of metal elements in the metal solution in this application are preferably five. More preferably, Ti3C2T x The molar ratios of MXene to Fe, Co, Ni, Cu, and Mn are (0.5-1):(1-1.2):(1-1.2):(1-1.2):(1-1.2):(1-1.2). Therefore, Ti3C2T xThe molar ratio of MXene to Fe, Co, Ni, Cu, and Mn can be 0.5:1:1:1:1:1:1, 0.6:1.1:1.1:1.1:1.1:1.1, 1:1:1:1:1:1:1, 1:1.2:1.2:1.2:1.2:1.2, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges in other embodiments.
[0053] In some embodiments of the present application, in step 5, the annealing temperature is 500-800°C, the heating rate is 3-6°C / min, and the holding time is 1-3h. When the temperature is low, the crystallinity of the oxide is weak, and the metal-oxygen binding force is weak, which will lead to poor stability of the electrode material. When the temperature is high, the crystallinity of the oxide is strong. Although the stability is improved, it is not conducive to the interaction between the electrode reaction interface and the reaction intermediates, and the catalytic performance will be adversely affected. Therefore, the annealing temperature can be 500°C, 600°C, 700°C, 800°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges in other embodiments.
[0054] In some embodiments of the present application, the average particle size of the electrode material is 30 to 50 nm.
[0055] 2. Application of a high-performance MXene-modified oxide water electrolysis electrode
[0056] The electrode described in the present application is used as a catalyst for electrolyzing water or seawater, and is particularly suitable for use as a catalyst for electrolyzing seawater.
[0057] 3. Examples and Comparative Examples
[0058] Example 1
[0059] Step 1: Preparation of Ti3AlC2 MAX powder
[0060] Titanium powder, aluminum powder and carbon powder (the molar ratio of titanium powder, aluminum powder and carbon powder is 3:1.2:1.9) are mixed and stirred evenly, and the mixed powder is sintered in a weak oxidizing atmosphere (oxygen content is less than 0.001%) at a sintering temperature of 1500°C for 4 hours. After completion, the powder is crushed and ground to obtain Ti3AlC2 MAX powder.
[0061] Step 2: Multilayer Accordion-like Ti3C2T x Preparation of MXene
[0062] The Ti3AlC2 MAX powder obtained in step 1 was mixed with a hydrofluoric acid solution at a solid-liquid ratio of 1:15; the water bath temperature was 45°C, the stirring time was 48 hours, and then the suspension after the reaction was centrifuged, the precipitate was repeatedly centrifuged and washed, filtered, and vacuum dried to obtain a multi-layer accordion-shaped Ti3C2T x MXene.
[0063] Step 3: 2D Ti3C2T x Preparation of MXene suspension
[0064] Take the multilayer accordion-shaped Ti3C2T obtained in step 2 x MXene, mixed with tetramethylammonium hydroxide intercalant, multilayer accordion-like Ti3AlC2T x The mass volume ratio of MXene to intercalant was 1 g: 20 mL. The suspension was obtained by stirring and centrifuging. The precipitate was retained and repeatedly dispersed with deionized water to obtain a two-dimensional lamellar Ti3C2T x MXene suspension.
[0065] Step 4: Preparation of MXene-modified oxide water electrolysis electrode precursor
[0066] The suspension prepared in step 3 is mixed with a metal salt solution and an organic ligand in a methanol solution for reaction, the product after the reaction is centrifuged, and the precipitate is repeatedly washed and vacuum dried to obtain a reaction precursor; wherein Ti3C2T x The molar ratio of MXene to Fe, Co, Ni, Cu and Mn is 0.5:1:1:1:1:1:1; the metal salt solution is a mixture of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O and Mn(NO3)2·4H2O; the organic ligand is terephthalic acid, and the concentration of the organic ligand in the reaction system is 0.3mmol / mL; the reaction temperature is 60°C, the reaction time is 24h, and then the suspension after the reaction is centrifuged, the precipitate is taken and repeatedly washed, and the reaction precursor is obtained after vacuum drying.
[0067] Step 5: Preparation of MXene-modified oxide water electrolysis electrode
[0068] The precursor obtained in step 4 is placed in the middle of a tube furnace and annealed in an air atmosphere at a temperature of 600° C., a heating rate of 5° C. / min, and a holding time of 2 h to obtain the high-performance MXene-modified oxide water electrolysis electrode.
[0069] Example 2
[0070] The improvement is made on the basis of Example 1, except that: in step 4, the metal salts are Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and Cu(NO3)2·3H2O in equimolar amounts (a total of 5 mmol for the four metal salts). The other steps are exactly the same as those in Example 1.
[0071] Example 3
[0072] The improvement is made on the basis of Example 1, except that: in step 4, the metal salt is Fe(NO3)2·9H2O, Co(NO3)2·6H2O, and Cu(NO3)2·3H2O in equimolar amounts (three metal salts totaling 5 mmol). The other steps are exactly the same as those in Example 1.
[0073] Example 4
[0074] The improvement is made on the basis of Example 1, except that in step 4, the metal salt is Co(NO3)2·6H2O and Cu(NO3)2·3H2O in equimolar amounts (two metal salts totaling 5 mmol). The other steps are exactly the same as those in Example 1.
[0075] Example 5
[0076] The improvement is made on the basis of Example 1, and the difference is that in step 4, the metal salt is Co(NO3)2·6H2O (a metal salt totaling 5 mmol). The other steps are exactly the same as those in Example 1.
[0077] Comparative Example 1
[0078] The improvement is made on the basis of Example 1, and the difference therefrom is that: in step 4, no MXene suspension is added. The other steps are exactly the same as those in Example 1.
[0079] Comparative Example 2
[0080] The improvement was made on the basis of Example 2, except that: in step 4, no MXene suspension was added, and the metal salts were equimolar (5 mmol in total) of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, and Cu(NO3)2·3H2O. The other steps were exactly the same as those in Example 2.
[0081] Comparative Example 3
[0082] The improvement was made on the basis of Example 3, except that: in step 4, no MXene suspension was added, and the metal salts were equimolar (5 mmol in total) of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, and Cu(NO3)2·3H2O. The other steps were exactly the same as those in Example 3.
[0083] Comparative Example 4
[0084] The improvement was made on the basis of Example 4, except that: in step 4, no MXene suspension was added, and the metal salt was Co(NO3)2·6H2O and Cu(NO3)2·3H2O in equimolar (5 mmol in total). The other steps were exactly the same as those in Example 4.
[0085] Comparative Example 5
[0086] The improvement was made on the basis of Example 5, except that: in step 4, no MXene suspension was added, and the metal salt was 5 mmol of Co(NO3)2·6H2O. The other steps were exactly the same as those in Example 5.
[0087] 4. Electrode morphology and performance analysis
[0088] 1. Microscopic analysis
[0089] Example 1 was placed on a Talos F200S transmission electron microscope for microscopic morphology observation. Figure 1 As shown, high-density and dispersed oxide (HEO) nanoparticles are uniformly loaded on the MXene layer, and the diameter of the nanoparticles is about 30nm. This structure greatly improves the dispersion of HEO nanoparticles and provides more available active sites, allowing reactants and products to diffuse and exchange quickly. This is conducive to rapid electron transfer and improved electrocatalytic performance. Figure 2 This is a high-resolution transmission electron microscope image. It can be seen from the figure that these nanoparticles are polycrystalline. and The lattice fringes correspond to the (311) and (222) planes of the y-Fe2O3 phase, which is consistent with the standard value and There is a deviation compared to the above, which may be due to the fact that multiple metal elements are dissolved in Example 1, resulting in lattice distortion and some point defects.
[0090] 2. Electrochemical performance test in alkaline medium
[0091] The LSV curves of the examples and comparative examples were measured on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. A three-electrode system was used to test the oxygen evolution performance, with the examples and comparative examples as working electrodes, a graphite rod as a counter electrode, Hg / HgO as a reference electrode, and a 1 mol / L KOH solution as the electrolyte.
[0092] Table 1 Electrochemical measurement results of the electrodes of the embodiments and different comparative examples in alkaline medium
[0093]
[0094]
[0095] Depend on Figure 3 , Figure 4 As can be seen from Table 1, the oxygen evolution overpotential and Tafel slope of the examples of the present application have both been greatly reduced, which are significantly lower than those of the corresponding comparative examples. This shows that the MXene modified oxide electrode obtained in the present application has excellent catalytic performance and good reaction kinetics in alkaline media.
[0096] 3. Electrochemical performance test in alkaline simulated seawater medium
[0097] The LSV curves of the embodiments and comparative examples were measured on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. A three-electrode system was used to test the oxygen evolution performance, with the embodiments and comparative examples as working electrodes, a graphite rod as a counter electrode, Hg / HgO as a reference electrode, and an electrolyte of a mixed solution of 1 mol / L KOH and 0.5 mol / L NaCl.
[0098] Table 2 Electrochemical measurement results of the electrodes of the embodiments and different comparative examples in alkaline simulated seawater medium
[0099]
[0100] Depend on Figure 5 , Figure 6 As can be seen from Table 2, the oxygen evolution overpotential and Tafel slope of the examples of the present application have both been greatly reduced, which are significantly lower than those of the corresponding comparative examples. This shows that the MXene-modified oxide electrode obtained in the present application has excellent catalytic performance and good reaction kinetic conditions in alkaline simulated seawater medium.
[0101] 4. Determination of electrochemical specific surface area
[0102] The examples and comparative examples were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure the cyclic voltammetry curves (CV curves). The electrochemical specific surface area (Cdl ).
[0103] Table 3 Electrochemical specific surface area measurement results of the electrodes of the embodiments and different comparative examples
[0104]
[0105]
[0106] Depend on Figure 7 As can be seen from Table 3, Comparative Examples 1 to 5 only performed one step of the method described in the present application, and such treatment had a very limited effect on the improvement of the electrochemical specific surface area. However, the embodiment of the present application greatly improved the electrochemical specific surface area of the electrode through MXene modification, increasing the electrochemical specific surface area to 2.69 mF·cm -2 .
[0107] 5. Determination of electrochemical stability
[0108] In addition to activity, the most critical catalytic performance indicator is stability. Figure 8 The results of long-term continuous chronopotentiometry tests of Example 1 and Comparative Example 1 in alkaline simulated seawater medium are shown. After long-term operation, the catalyst of Example 1 still has excellent activity, while Comparative Example 1 gradually deactivates. The above tests show that the electrode of the present invention can improve the corrosion resistance, which is because MXene exhibits good Coulomb repulsion to chloride ions.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.
Claims
1. A high-performance MXene-modified oxide water electrolysis electrode, characterized in that: The electrode is prepared by the following steps: Step 1: Prepare Ti3AlC2 MAX powder; Step 2: Mix the Ti3AlC2 MAX powder prepared in step 1 with the hydrofluoric acid solution and heat to 45-50°C for reaction while stirring continuously. Wash and dry the solid material to obtain a multilayer accordion-shaped Ti3AlC2T x MXene; Step 3: Take the Ti3AlC2T prepared in step 2 x MXene and the intercalation agent are mixed and stirred evenly to obtain a suspension, which is then centrifuged and the precipitate is repeatedly dispersed with water to obtain a two-dimensional lamellar Ti3C2T x MXene suspension; wherein the intercalation agent is tetramethylammonium hydroxide, and the mass concentration of the intercalation agent is 10wt%-15wt% calculated by mass percentage; Ti3AlC2T x The mass volume ratio of MXene to intercalant is 1 g: (10-40) mL; Step 4: mixing the suspension prepared in step 3 with the metal salt solution and the organic ligand in a methanol solution for reaction, centrifuging the product after the reaction, taking the precipitate, repeatedly washing it and vacuum drying it to obtain a reaction precursor; Among them, Ti3C2T x The molar ratio of MXene to the metal element in the metal salt solution is (0.5-1):5; the metal salt solution is one or a mixture of two or more of Fe(NO3)2·9H2O, Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Cu(NO3)2·3H2O and Mn(NO3)2·4H2O; the organic ligand is terephthalic acid, and the concentration of the organic ligand in the reaction system is 0.3-0.4mmol / mL; the reaction temperature is 50-70°C, and the reaction time is 22-26h; Step 5: Annealing the precursor prepared in step 4 in an air atmosphere to obtain the water electrolysis electrode.
2. The electrode according to claim 1, characterized in that: In step 1, Ti3AlC2MAX powder is prepared by the following method: The titanium powder, aluminum powder and carbon powder are uniformly mixed, and the mixed powder is sintered, crushed and ground in a weak oxidizing atmosphere to obtain Ti3AlC2 MAX powder; The molar ratio of titanium powder, aluminum powder and carbon powder is 3:(1-1.5):(1-1.5); the gas flow rate is 150-250cm 3 / min; during sintering, the sintering temperature is 1300-1500°C and the sintering time is 6-12h; the particle size of the Ti3AlC2 MAX powder obtained by sintering is 50-100μm; the weak oxidizing atmosphere is calculated according to mass percentage, and the oxygen content in the atmosphere is less than 0.001%.
3. The electrode according to claim 2, characterized in that: In step 1, the heating rate from room temperature to 1200° C. is 10° C. / min, and the heating rate from 1200° C. to the sintering temperature is 2° C. / min.
4. The electrode according to claim 1, characterized in that: In step 2, calculated by mass percentage, the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 40% to 50%; the mass volume ratio of Ti3AlC2 MAX powder to the hydrofluoric acid solution is 1 g: (10 to 20) mL; and the reaction time is 48 h.
5. The electrode according to claim 1, characterized in that: In step 3, the suspension is centrifuged to obtain a supernatant having a pH value of 6-8.
6. The electrode according to claim 1, characterized in that: In step 4, when there are any two metal elements in the metal salt solution, the molar ratio of the two metal elements is (1-1.2):(1-1.2); when there are any three metal elements in the metal salt solution, the molar ratio of the three metal elements is (1-1.2):(1-1.2):(1-1.2); when there are any four metal elements in the metal salt solution, the molar ratio of the four metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2); when there are five metal elements in the metal salt solution, the molar ratio of the five metal elements is (1-1.2):(1-1.2):(1-1.2):(1-1.2).
7. The electrode according to claim 6, characterized in that: In step 4, Ti3C2T x The molar ratio between MXene and Fe, Co, Ni, Cu, and Mn is (0.5~1):(1~1.2):(1~1.2):(1~1.2):(1~1.2):(1~1.2).
8. The electrode according to claim 1, characterized in that: In step 5, the annealing temperature is 500-800° C., the heating rate is 3-6° C. / min, and the holding time of the annealing treatment is 1-3 h.
9. The electrode according to claim 1, characterized in that: The average particle size of the electrode material is 30 to 50 nm.
10. Application of a high-performance MXene-modified oxide water electrolysis electrode, characterized in that: The electrode according to any one of claims 1 to 9 is used as a catalyst for electrolysis of water or seawater.
Citation Information
Cited By
Anatase type TiO2 loaded RuCo nanocluster composite material as well as preparation method and application thereof
CN120094606A